Genetics and African Historiography: Limitations and Insights - (:unkn) unknown (My University, 2022)
Genetics and genomics are increasingly employed in studies which construct chronological narratives treated as a form of history, or used to comment on the ancestry of living groups which is then viewed in some historical fashion which might sometimes be viewed as “origins” a term with various possible meanings and problems (Bloch 1953). Ancient DNA has also been deployed in such situations despite poor (and inadequate) sample sizes in general, and gain their greatest legitimacy when species level i.e. macro-evolutionary questions are being examined. Here the major concern involves questions about human populations for which there is some notion of identity, if only geographical, and in general there will be no further mention of human evolutionary history in the usual sense. Many studies on Holocene populations have been carried out. The data for such work in the past were often and still are in some situations morphological and morphometric observations, which can still be useful given that ancient DNA (aDNA) work is in its infancy. Molecular studies include understanding the phylogeny of genetic variants or lineages themselves versus a concern with the populations in which they are found.
Keywords: African Research